Direct and Reverse Pluronic Micelles: Design and Characterization of Promising Drug Delivery Nanosystems - Almudena Naharros-Molinero; María Ángela Caballo-González; Francisco Javier de la Mata; Sandra García-Gallego (MDPI AG, 2022)
Pluronics are a family of amphiphilic block copolymers broadly explored in the pharmaceutical field. Under certain conditions, Pluronics self-assemble in different structures including nanosized direct and reverse micelles. This review provides an overview about the main parameters affecting the micellization process of Pluronics, such as polymer length, fragments distribution within the chain, solvents, additives and loading of cargo. Furthermore, it offers a guide about the most common techniques used to characterize the structure and properties of the micelles. Finally, it presents up-to-date approaches to improve the stability and drug loading of Pluronic micelles. Special attention is paid to reverse Pluronics and reverse micelles, currently underexplored in the literature. Pluronic micelles present a bright future as drug delivery agents. A smart design and thorough characterization will improve the transfer to clinical applications.